2016
DOI: 10.1016/j.jacc.2016.02.033
|View full text |Cite
|
Sign up to set email alerts
|

Early Aldosterone Blockade in Acute Myocardial Infarction

Abstract: The study failed to show the benefit of early MRA use in addition to standard therapy in patients admitted for MI. (Aldosterone Lethal effects Blockade in Acute myocardial infarction Treated with or without Reperfusion to improve Outcome and Survival at Six months follow-up; NCT01059136).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(75 citation statements)
references
References 23 publications
3
68
0
4
Order By: Relevance
“…Because the ALBATROSS trial suggested that early aldosterone antagonism might be beneficial in patients with ST elevation myocardial infarction without heart failure,18 we performed a sensitivity analysis on the 1757 patients who presented with ST elevation myocardial infarction. Similar to the full cohort, a doubling of aldosterone was not associated with the primary composite endpoint in this subset of patients (hazard ratio 0.91, 95% CI 0.70‐1.19, P =0.48).…”
Section: Resultsmentioning
confidence: 99%
“…Because the ALBATROSS trial suggested that early aldosterone antagonism might be beneficial in patients with ST elevation myocardial infarction without heart failure,18 we performed a sensitivity analysis on the 1757 patients who presented with ST elevation myocardial infarction. Similar to the full cohort, a doubling of aldosterone was not associated with the primary composite endpoint in this subset of patients (hazard ratio 0.91, 95% CI 0.70‐1.19, P =0.48).…”
Section: Resultsmentioning
confidence: 99%
“…This acute damage is followed by gradual repair with fibrosis. 6,27,28 Whether this strategy improves outcomes in patients without systolic dysfunction or symptomatic heart failure is yet to be determined. 23,24 Myocardial fibrosis may represent a major pathway leading to adverse remodelling, cardiac dysfunction, and worse prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The non-infarct zone exhibits reactive hypertrophy, interstitial fibrosis, and increased collagen, potentially leading to cardiac dysfunction. 27,28 Natriuretic peptides, such as BNP, are produced by cardiomyocytes and may be increased by cardiac and atrial stretch, and also by other factors, such as renal impairment or atrial fibrillation. 25,26 Thus, identifying patients more prone to adverse remodelling and DD may help clinicians in tailoring treatments with anti-adverse remodelling properties.…”
Section: Discussionmentioning
confidence: 99%
“…В дальнейшем в ходе выполнения РКИ АLBATROSS (Aldosterone Lethal effects Blocked in Acute MI Treated with or without Reperfusion to improve Outcome and Survival at Six months follow-up) оценивали эффективность применения альдостерона по сравнению с плацебо в ранние сроки после развития ОИМпST у больных с сохраненной ФВ ЛЖ [20]. В это исследование также было включено относительно небольшое число больных (n=1603), что, как и в исследовании REMINDER, затрудняло получение положительных результатов вследствие недостаточной статистической мощности.…”
Section: новые данные о прогностическом значении и роли повышения биоunclassified